Carcass and Chemical Quality of IPB D1 Chicken Meat in Free-range and Intensive Systems - Dewi Kartika; Niken Ulupi; Rudi Afnan; Zakiah Wulandari (Institut Pertanian Bogor, 2025)
IPB D1 chicken is a local chicken resulting from crossing pelung, sentul, kampung, and parent stock broiler strain Cobb chickens. IPB D1 chicken was released through a decree by the Ministry of Agriculture with No. 693/KPTS/PK. 230.M/9/2019. Free-range is a system of raising farm animals, including chickens, by providing access to outdoor running (pasture) to exercise, find more feed, and be exposed to more oxygen. This study analyzed the carcass percentage, edible carcass, non-edible carcass, and chemical quality of IPB D1 chickens raised in a free-range system. A total of 50 IPB D1 male chickens were raised in free-range and intensive systems for four weeks. The microclimatic data were analyzed descriptively. Meanwhile, carcass percentage and physicochemical and organoleptic properties of IPB D1 chicken meat were subjected to a t-test. Free-range and intensive systems showed no significant effects on the carcass, commercial cuts, edible and non-edible percentages, and MDA quality traits of IPB D1 male chicken thigh meat. The cholesterol content of IPB D1 thigh meat in a free-range system was significantly lower than in an intensive system Keywords: carcass, free-range, IPB D1 chicken, cholesterol, MDA